Smart ENT: Electrical & electronic training service and arduino kits supplier / Mohd Danish Irfan Mohd Sufian ... [et al.] - Mohd Sufian, Mohd Danish Irfan; Lut, Lutfiah Hanim; Mohd Khairul Lutfi, Nur 'Alyaa Diyanah; Abdul Rashid, Ayreen Sofea; Zulkifli, Aini Rasyidah (2017)
Smart Enterprise is multi purpose business that provides services in training about electrical and electronic, while we providing starter kit and advance kit and we will be establish in early 2018.Our business is expected to commence on 2018 and our vision is to be the best helper for development. This will be realized by the full cooperation and efforts among the partners to promote company. We will expect that our business will become more developed in the near future because our daily operation is decided to be longer than other electrical company. We operate for 8 hours a day so that customers do not have to be in a hurry to steal time. From time to time, we will find new strategies to attract more customers and making them loyal customers. This will give more advantages for us to make our product more profitable and stable in the long run.